Perancangan Sistem Informasi Perawatan Mesin Pada PT XYZ - Berry Yuliandra; Kushisa Atta Jaeba (Universitas Katolik Parahyangan, 2017)
Maintenance management is an important aspect that define success and sustainability of a manufacturing industry. The development of information technology give new possibilities to improve maintenance management performance. Data management with the help from information system will improve maintenance management effectiveness and efficiency. PT XYZ is an industry specialized in retreading tires service. Preliminary study on machinery maintenance process in PT XYZ showed that breakdown and maintenance data were not properly documented. This can generate high cost for the company because maintenance scheduling cannot optimally determined and the cost incurred by repair and maintenance activities, and also the cost of lost production time cannot determined directly. Therefore PT XYZ need information system to improve their maintenance management efficiency. Information system designed in accordance with company need based on system survey and interview. The design of information system developed using Object Oriented Analysis (OOA) and Object Oriented Design (OOD) approach. The designed information system can help maintenance management implementation and related data management. The availability of repair and maintenance data can help factory supervisor to make decision related to maintenance activities such as parts needed and maintenance cost.Keywords: maintenance, information system, performance